2021
DOI: 10.1002/anie.202102160
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Protease Activation on a Multimeric Synthetic Protein Scaffold via Adaptable DNA‐Based Recruitment Domains

Abstract: Hexameric hemoprotein (HTHP) is employed as a scaffold protein for the supramolecular assembly and activation of the apoptotic signalling enzyme caspase‐9, using short DNA elements as modular recruitment domains. Caspase‐9 assembly and activation on the HTHP platform due to enhanced proximity is followed by combinatorial inhibition at high scaffold concentrations. The DNA recruitment domains allow for reversible switching of the caspase‐9 assembly and activity state using short modulatory DNA strands. Tuning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The increase observed on product formation at larger protein excesses might occur due to protein aggregation which leads to a non-specific colocalization of reactants, in accordance with previous observations. [42] Small 2023, 19, 2200971 A series of control experiments further supports that the reaction is templated by HSA (Figure S3, Supporting Information). A specificity test shows that the system is solely responsive to HSA, as no product is generated in the presence of other proteins (i.e., bovine serum albumin, BSA) (Figure S3, lane 3, Supporting Information).…”
Section: Chemical Reactions Templated By Proteins and Mathematical Modelmentioning
confidence: 75%
See 1 more Smart Citation
“…The increase observed on product formation at larger protein excesses might occur due to protein aggregation which leads to a non-specific colocalization of reactants, in accordance with previous observations. [42] Small 2023, 19, 2200971 A series of control experiments further supports that the reaction is templated by HSA (Figure S3, Supporting Information). A specificity test shows that the system is solely responsive to HSA, as no product is generated in the presence of other proteins (i.e., bovine serum albumin, BSA) (Figure S3, lane 3, Supporting Information).…”
Section: Chemical Reactions Templated By Proteins and Mathematical Modelmentioning
confidence: 75%
“…The increase observed on product formation at larger protein excesses might occur due to protein aggregation which leads to a non‐specific colocalization of reactants, in accordance with previous observations. [ 42 ]…”
Section: Resultsmentioning
confidence: 99%
“…Recently, de Greef et al. have shown that DNA‐mediated dimerization can lead to the activation of caspase‐9, an enzyme involved in apoptosis [5c,14] . These studies have shed fundamental insight into proximity‐driven enzyme regulation and its possible role in programmed cell death.…”
Section: Dna As a Scaffold For Protein Assemblymentioning
confidence: 99%
“…The complex, tightly regulated networks [1, 2] through which DNA, RNA and proteins interact underly the functioning of living systems [3–5] . One of the aims of synthetic biology is to create artificial pathways in which DNA, RNA and proteins interact with each other via analogously “programmed” reaction patterns to create new tools for sensing, drug‐delivery, cell imaging [6–14] . A widely used approach to this end is the rational design of synthetic DNA/protein communication that takes advantage of the many naturally occurring proteins that recognize and bind specific oligonucleotide sequences to, for example, regulate transcription or translation [15–21] .…”
Section: Figurementioning
confidence: 99%